Analysis of the passive biomechanical behavior of a sheep-specific aortic artery in pulsatile flow conditions. Issue 11 (8th September 2021) - García–Herrera, Claudio M.; Cuevas, Álvaro A.; Celentano, Diego J.; Navarrete, Álvaro; Aranda, Pedro; Herrera, Emilio; Uribe, Sergio
Abstract: In this work, a novel numerical-experimental procedure is proposed, through the use of the Cardiac Simulation Test (CST), device that allows the exposure of the arterial tissue to in-vitro conditions, mimicking cardiac cycles generated by the heart. The main goal is to describe mechanical response of the arterial wall under physiological conditions, when it is subjected to a variable pressure wave over time, which causes a stress state affecting the biomechanical behavior of the artery wall. In order to get information related to stress and strain states, numerical simulation via finite element method, is performed under a condition of systolic and diastolic pressure. The description of this methodological procedure is performed with a sample corresponding to a sheep aorta without cardiovascular pathologies. There are two major findings: the evaluation of the mechanical properties of the sheep aorta through the above-mentioned tests and, the numerical simulation of the mechanical response under the conditions present in the CST. The results state that differences between numerical and experimental circumferential stretch in diastole and systole to distinct zones studied do not exceed 1%. However, greater discrepancies can be seen in the distensibility and incremental modulus, two main indicators, which are in the order of 30%. In addition, numerical results determine an increase of the principal maximum stress and strain between the case of systolic and diastolic pressure, corresponding to 31.1% and 14.9% for the stress and strain measurement respectively; where maximum values of these variables are located in the zone of the ascending aorta and the aortic arch.